Lifetime maps for orbits around Callisto using a double-averaged model - Cardosodossantos, Josué [UNESP] (2017)
The present paper studies the lifetime of orbits around a moon that is in orbit around its mother planet. In the context of the inner restricted three-body problem, the dynamical model considered in the present study uses the double-averaged dynamics of a spacecraft moving around a moon under the gravitational pulling of a disturbing third body in an elliptical orbit. The non-uniform distribution of the mass of the moon is also considered. Applications are performed using numerical experiments for the Callisto–spacecraft–Jupiter system, and lifetime maps for different values of the eccentricity of the disturbing body (Jupiter) are presented, in order to investigate the role of this parameter in these maps. The idea is to simulate a system with the same physical parameters as the Jupiter–Callisto system, but with larger eccentricities. These maps are also useful for validation and improvements in the results available in the literature, such as to find conditions to extend the available time for a massless orbiting body to be in highly inclined orbits under gravitational disturbances coming from the other bodies of the system.